Hydraulic Fracturing Treatment Optimization for Low Permeability Reservoirs Based on Unified Fracture Design - Kun Ai; Longchen Duan; Hui Gao; Guangliang Jia (Energies, 2018)
Hydraulic fracturing optimization is very important for low permeability reservoir stimulation and development. This paper couples the fracturing treatment optimization with fracture geometry optimization in order to maximize the dimensionless productivity index. The optimal fracture dimensions and optimal dimensionless fracture conductivity, given a certain mass or volume of proppant, can be determined by Unified Fracture Design (UFD) method. When solving the optimal propped fracture length and width, the volume and permeability of the propped fracture should be determined first. However, they vary according to the proppant concentration in the fracture and cannot be obtained in advance. This paper proposes an iterative method to obtain the volume and permeability of propped fractures according to a desired proppant concentration. By introducing the desired proppant concentration, this paper proposes a rapid semi-analytical fracture propagation model, which can optimize fracture treatment parameters such as pad fluid volume, injection rate, fluid rheological parameters, and proppant pumping schedule. This is achieved via an interval search method so as to satisfy the optimal fracture conductivity and dimensions. Case study validation is conducted to demonstrate that this method can obtain optimal solutions under various constraints in order to meet different treatment conditions.